Miscarriage of Justice in Corporate Fraud Cases: The Legal Paradox of the Herlambang Gold Transaction in Indonesia - Lyanawati, Yuli Maria; Borman, M.Syahrul; Cornelis, Vieta Imelda (PT. Anagata Sembagi Education, 2026)
This article examines a high value gold transaction dispute that illustrates how fragmented judicial reasoning, prosecutorial discretion, and corporate governance failures can converge to produce a miscarriage of justice in complex economic-crime cases. Using a socio-legal case study approach, the analysis reconstructs a transaction in which a buyer paid IDR 1.2 trillion for 4,000 kilograms of gold but received only 2,400 kilograms, a shortfall acknowledged by the selling corporation in civil proceedings. Early criminal cases convicted corporate insiders for fraud, recognizing the buyer as a victim. However, subsequent corruption proceedings reversed this position, alleging without evidentiary support that the buyer unlawfully obtained excess gold and caused state financial loss. Criminal courts accepted this narrative despite auditor testimony confirming the absence of state loss and despite inconsistencies with civil judgments. The findings reveal four systemic weaknesses: disregard of documentary evidence, role inversion from victim to offender, contradictory civil–criminal outcomes, and liability shifting driven by corporate governance failures. These dynamics align with broader patterns of wrongful convictions in economic-crime contexts. The study underscores the need for stronger evidentiary standards, improved inter-court coordination, enhanced forensic capacity, and clearer boundaries between commercial disputes and corruption enforcement